Rural development in the context of internal population movement - Mihaela-Georgiana Oprea; Carmen-Adriana Gheorghe; Mihaela-Irma Vlădescu (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
According to the possibilities offered by the existing resources, rural development in Romania is still difficult to achieve. The economic-social gaps between the urban and rural areas are among the highest in the EU and relatively at the same amplitude for many years. The recent period, marked by multiple crises (of a sanitary, economic and social nature) has shown that the development of the rural area is reduced, on the one hand due to the economic structure and labor resources inadequate to changes and shocks, and on the other hand due to income inequality, respectively of the low remuneration in agriculture, compared to non-agricultural activities. The demographic developments in recent years, relatively contradictory, flows of young population to certain localities in the rural areas, simultaneously with a more pronounced aging in many other rural areas, require differentiated policies and programs for each area depending on the specific local demographics. The lack of an approach adapted to local demographic developments reduced the effectiveness of rural development programs. The study will highlight the dependence of demographic developments in rural areas on the level of development; in the rural environment of the less developed counties, the aging of the population is accentuated by the emigration of young people. The more developed areas benefit from an influx made up mostly of the young population who have migrated from the urban environment and contribute to the development of the adopted localities. After 2015 the rate of internal migration from urban to rural was high in relation to the flow between rural and urban. For example, in 2020, the peak pandemic year, the migration rate from urban to rural was 12.1 per 1000 inhabitants compared to only 6.2 per 1000 inhabitants the migration rate from rural to urban. The study also highlights the correlation between the specifics of demographic developments and progress in the employment of rural labor resource. In this context, we underline the fact that the incomes of rural households were around 62% of the average income per person in urban households.
Keywords: J60; O13; R11; R21; 330; rural development; gaps; demographic developments; income; labor force